Human Resource Risk Management in Construction Services Companies in Bojonegoro - Rodhi, Nova Nevila (Jurnal Teknologi dan Manajemen, 2025)
The success of a construction service company is influenced by human resources. However, in its implementation, human resources have risks that can also have a negative impact on the company. Therefore, the purpose of this study is to analyze the risk of human resources in construction service companies in Bojonegoro using the probability impact matrix method. The results obtained are that there are 17 (seventeen) risk factors that have been identified, which are divided into low, medium and high levels. By knowing the risk level, a management action can be taken in the form of a transfer action for low risk factors, for risks at the medium level, reduction (mitigation) actions can be taken, and for risk factors at the high level, avoidance actions can be taken